2018
DOI: 10.1371/journal.pone.0199304
|View full text |Cite
|
Sign up to set email alerts
|

Urban sanitation coverage and environmental fecal contamination: Links between the household and public environments of Accra, Ghana

Abstract: Exposure to fecal contamination in public areas, especially in dense, urban environments, may significantly contribute to enteric infection risk. This study examined associations between sanitation and fecal contamination in public environments in four low-income neighborhoods in Accra, Ghana. Soil (n = 72) and open drain (n = 90) samples were tested for E. coli, adenovirus, and norovirus. Sanitation facilities in surveyed households (n = 793) were categorized by onsite fecal sludge containment (“contained” vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 69 publications
0
32
0
2
Order By: Relevance
“…Each visit had a window to enable follow-up if the infant was not seen on the target date. Environmental enteric dysfunction in Zimbabwean children in WASH coverage are associated with reductions in environmental faecal contamination [83]. In addition, exposure to animal rather than human excreta may represent a larger source of faecal contamination [84].…”
Section: Geometric Means Pointwise 95% Confidence Intervals and The mentioning
confidence: 99%
“…Each visit had a window to enable follow-up if the infant was not seen on the target date. Environmental enteric dysfunction in Zimbabwean children in WASH coverage are associated with reductions in environmental faecal contamination [83]. In addition, exposure to animal rather than human excreta may represent a larger source of faecal contamination [84].…”
Section: Geometric Means Pointwise 95% Confidence Intervals and The mentioning
confidence: 99%
“…Other activities such as discharge of faecal waste during the rainy season can also lead to the contamination of soil. A study in an urban slum in Uganda found higher levels of E. coli (5.4 log10 CFU per g), compared to this study during the dry season, but there, samples were taken specifically from open spaces and the playgrounds of children [ 33 ]. Children face considerable risk from soil during the dry season, this is because they spend most of the time playing outside on the ground.…”
Section: Resultsmentioning
confidence: 80%
“…This seasonal variation was found to be significantly different ( p ≤ 0.05, Table 2 ). The only other study that explored seasonal variation in E. coli concentration in open drains was from Ghana, though they did not find any variations, and the study looked at two rainy seasons [ 33 ]. The results are surprising because it would have been expected that the risk would have been higher during the rainy season than the dry season because it has been observed that most elevated latrines in Kampala have an opening at the back which is used to empty faecal sludge into adjacent open drains, in addition to the washing effect of rain [ 30 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…La exposición a la contaminación fecal en áreas públicas, especialmente en entornos urbanos densos, puede contribuir significativamente al riesgo de infección entérica. Berendes et al (2018) examinaron las asociaciones entre el saneamiento y la contaminación fecal en entornos públicos en cuatro barrios de bajos ingresos en Ghana. Los autores hallaron una mayor concentración de microorganismos fecales en áreas con escasa infraestructura sanitaria.…”
Section: 6-aspectos Espaciales Y Temporales De Las Enfermedades Diaunclassified